SOCIAL DEFENCE OF CHILDREN SUFFERED IN THE RESULT OF MILITARY ACTIONS AND ARMED CONFLICTS: CONCEPT AND FEATURES - Beluga, Yuliia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: to define a concept and the features of social defence of children suffered in the result of military actions and armed conflicts. Methods: formal-logical method, system analysis method, structural-functional method, historical and other research methods. Results: analising the various scientific approaches, an author considers the essence and features of the categories «social defence» and «social security», defines a concept and the features of social defence of children suffered in the result of military actions and armed conflicts. Discussion: a legal discussion in the article is about the definition of a legal category for the designation of social defence of children suffered in the result of military actions and armed conflicts. It is justified that «social defence» is a concept that the most fully reflects the derived constituent elements: social security, social guarantees, social benefits, social adaptation and social rehabilitation. Social defence of children is one of the main tasks of our state, because the level of their safety and comprehensive development is an indicator of the level of development of the country. In view of physical development, psychological state, age, life inexperience, children need legal and social protection in the first place. Recently, this issue deserves special attention, because our country is going through a period of war, so the issue of defending the rights and freedoms of children in conditions of armed aggression not only does not lose its relevance, but on the contrary, it is gaining more and more importance. A problem of social defence of children in recent years has attracted the attention of many scientists, scientists, lawyers and, in connection with the events taking place in the state, has shaken human society, which has finally begun to realize a need for the increased attention to children in general, and to each child in particular, who suffered in the result of military actions and armed conflicts. Determining the essence and features of social defence for children suffered in the result of military actions and armed conflicts acquires special relevance in the complex modern conditions, because social development and social defence are of the utmost importance for meeting needs and hopes all over the world. The very concept of «social protection» does not have a precise legal definition and needs further improvement. In the laws and other normative legal acts of Ukraine, there is no definition of the concept of social defence of children in the result of military actions and armed conflicts. The Constitution of Ukraine is the Basic Law on which the national legislation is based, a component of which is the legislation on social security. In accordance with the part 1 of Article 46 of the Constitution of Ukraine a concept «social defence» means «the right to security for citizens in case of total, partial or temporary loss of working capacity, loss of breadwinner, unemployment due to circumstances beyond their control, as well as in old age and in other cases determined for by the law».